Penyuluhan Pentingnya Konservasi Ekosistem Mangrove di Kampung Rawa Mekar Jaya Kabuparten Siak - Yusni Ikhwan Siregar; Mirna Ilza; Irvina Nurachmi; Rahmadi Rahmadi (PELANTAR PRESS, 2022)
As part of the coastal and marine environment, mangrove ecosystems are often degraded due to more levies/logging, the conversion of nikau forests into ponds shrimp, and pollution. The decline in the quality of this area originated from anthropogenic factors from land pollution originating from land (land base), as well as pollution from marine activities (seabase). The threat needs to be anticipated through increased awareness and awareness of key stakeholders (logging communities). In terms of environmental science, this ecosystem is seen as a potential bulwark of carbon and other environmental services. This activity is an effort to provide understanding to the general public and government officials about the various benefits and importance of mangrove conservation efforts. Counseling on this topic is very necessary because there is information about community complaints about the high exploitation and threats to the sustainability of its existence in Kampung Rawa Mekar Jaya, Siak Regency. Counseling is considered important to be carried out because of the increasing degradation of coastal ecosystems (mangroves, coastal waters, estuaries) due to environmental pressures from human activity. From this community service activity, it is hoped that it can increase the knowledge, understanding, and awareness of the local community about the benefits of long Janka to maintaining coastal and marine ecosystems. The mindset of coastal communities is expected to be open and understand what can be done, what can and cannot be done to coastlines and mangrove ecosystems, for the sake of preserving natural resources and the environment related to the lives of the general public and especially fishermen whose lives are largely dependent on these ecosystems. The form of this planned community service activity is counseling on the importance of mangrove forest ecosystem conservation as an effort to preserve the ecology of coastal areas and coastal waters of Kampung Rawa Mekar Jaya, Siak Regency. Counseling on this topic is considered very necessary considering the increasingly intense community activities that cause overexploitation of mangrove forest areas. This activity is one of the efforts to bring the name of Riau University into contributing to the development of community service specialties, especially education in the field of mangrove forest ecosystem management